1984
DOI: 10.1111/j.1476-5381.1984.tb16216.x
|View full text |Cite
|
Sign up to set email alerts
|

Triggering by Paf‐acether and adrenaline of cyclo‐oxygenase‐independent platelet aggregation

Abstract: Platelet‐activating factor (Paf‐acether, 1‐alkyl‐2‐acetyl‐sn‐glycero‐3‐phosphorylcholine) induced full aggregation and a limited release reaction of human platelets in plasma or in blood. Cyclo‐oxygenase inhibition with aspirin only reduced aggregation when induced by threshold amounts of Paf‐acether, whereas higher concentrations surmounted inhibition whether tested in citrated or in heparinized platelet‐rich plasma or blood. Aspirin‐induced inhibition of platelet secretion by Paf‐acether was insurmountable a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0
3

Year Published

1986
1986
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 24 publications
5
22
0
3
Order By: Relevance
“…Aspirin has also been shown to partially inhibit ex vivo PAF-induced platelet aggregation and ATP release (Lecrubier et al, 1983;Rao et al, 1982) . Dose dependent inhibition at low but not high concentrations of PAF has also been reported (Cattaneo et al, 1985;Fouque & Vargaftig, 1984;Macconi et al, 1985). As a result, the effect of aspirin on PAF-induced platelet aggregation remains unclear.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Aspirin has also been shown to partially inhibit ex vivo PAF-induced platelet aggregation and ATP release (Lecrubier et al, 1983;Rao et al, 1982) . Dose dependent inhibition at low but not high concentrations of PAF has also been reported (Cattaneo et al, 1985;Fouque & Vargaftig, 1984;Macconi et al, 1985). As a result, the effect of aspirin on PAF-induced platelet aggregation remains unclear.…”
Section: Introductionmentioning
confidence: 74%
“…In one study in which five healthy volunteers took 500 mg of aspirin daily for five days, there was no inhibition of PAF-induced aggregation . However, other investigators have shown aspirin inhibits aggregation induced by low concentrations of PAF but not at higher concentrations (Cattaneo et al, 1985;Fouque & Vargaftig, 1984;Macconi et al, 1985) and a recent study by McCulloch et al (1989) has suggested low dose aspirin can inhibit both platelet aggregation and release.…”
Section: Discussionmentioning
confidence: 99%
“…These concentrations were selected based on a previous study [2]. After 15–30 s of topical application of the vasodilators, their effects were measured.…”
Section: Methodsmentioning
confidence: 99%
“…A 500-line television camera (JVC, Tokyo, Japan) was coupled to a trinocular microscope (Zeiss, Oberkochen, Germany) to facilitate observation of the enlarged image (×3,400) on the video screen. The shearing of the image enables the measurement of the vascular diameter [2]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation